Design and synthesis of novel derivatives of 6β-hydroxy betunolic acid as antibacterial agents. (3rd December 2022) - Wickramasingha, W.G. Dilusha; Jayasinghe, Susanthi; Karunaratne, D. Nedra; Ekanayake, E.W.M. Asela; Liyanapathirana, Veranja; Senadeera, Sarath P.D.; Karunaratne, Veranja
Abstract: 6β-Hydroxy betunolic acid (1 ), has been identified as a novel, effective natural antibiotic lead compound, and hence, thirteen semisynthetic derivatives of 1 were synthesized including twelve novel compounds. Their structure-activity relationship was evaluated against sixteen pathogenic bacterial strains. Results revealed that the presence of a carboxylic acid group at C17 and unsaturation at C20–C29 are essential for the antibacterial activity of 6β-Hydroxy betunolic acid. Further, increased antibacterial activity was observed for 6β-hydroxy betunolic acid with acetyl modification at C3 against S. aureus and MRSA 114, however, none of the analogues including 6β-hydroxy betunolic acid showed antibacterial activity against the Gram-negative bacterial strains tested. Graphical abstract: Image 1 Highlights: Thirteen semisynthetic derivatives of 6β-hydroxy betunolic acid were synthesized. All the derivatives were evaluated for SAR on antibacterial activity. The C3 acetylated derivative had improved activity against Gram positives. All the derivatives were inactive towards Gram negative strains.